P‐176: Quantitative Analysis of Charge Transport in Single‐Carrier Devices and OLEDs Combining DC and AC Data. Issue 1 (29th May 2019) - Jenatsch, Sandra; Züfle, Simon; Will, Paul-Anton; Blülle, Balthasar; Neukom, Martin; Lenk, Simone; Reineke, Sebastian; Braga, Daniele; Domanski, Konrad; Ruhstaller, Beat
Abstract : Single‐carrier devices are perfect model systems to extract material parameters for more complex multilayer organic light‐emitting diodes (OLEDs) and to learn about charge transport and injection properties of the device. By combining simulation and measurements in steady‐state and frequency domain, we obtain a set of reliable material parameters which can be used to model the multilayer OLED structure. Moreover, we can also evaluate the contact behavior and conclude that the OLED operation is limited by electron transport.